The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1159/000186149
|View full text |Cite
|
Sign up to set email alerts
|

Production of Methylguanidine from Creatinine in Normal Rats and Rats with Renal Failure

Abstract: Creatinine (Cr) was administered intraperitoneally to both normal rats and those given adenine, and time-course changes in methylguanidine (MG) production from Cr were compared. In rats with renal failure, the accumulation of MG in the body increased gradually with time after Cr administration. In particular, the MG level in skeletal muscle was markedly high in comparison with that in serum, liver or kidney, and a high concentration of MG was still present 24 h after Cr loading. In contrast, the amount of MG e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Some experiments revealed that animals with high-level MG displayed a lot of functional and pathological characteristic features of uremia. 12,13 Another study showed significant reduction of the glomerular filtration rate, renal plasma flow, and renal blood flow after administration of MG to normal rats 14 and rats with adenine-induced chronic renal failure. 15 Thus, MG has apparent toxic effects on kidney and causes deterioration of renal function, but the pathogenesis is still not very well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Some experiments revealed that animals with high-level MG displayed a lot of functional and pathological characteristic features of uremia. 12,13 Another study showed significant reduction of the glomerular filtration rate, renal plasma flow, and renal blood flow after administration of MG to normal rats 14 and rats with adenine-induced chronic renal failure. 15 Thus, MG has apparent toxic effects on kidney and causes deterioration of renal function, but the pathogenesis is still not very well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Normal animals were fed on an 18% casein diet for 10 days. In rats given adenine, it had been confirmed previously both histologically and biochemi cally that renal failure progressed as the peri od of adenine feeding was prolonged [16][17][18][19][20][21][22][23]. The level of serum constituents in experimen tal rats were as follows: in rats fed on the adenine diet, urea nitrogen levels were 3.2 times (50.5 ±1.5 mg/dl) those in normal rats on the 10th experimental day, and 8.6 times higher on the 30th experimental day.…”
mentioning
confidence: 99%
“…It seems that the normal brain content of creatinine is very low but increases considerably in the presence of an extra creatinine load. Creatinine levels have been found to be increased in the brain of both uremic persons and experimental animals, with the latter suffering convulsions after intraperitoneal injection of creatinine (18,19). The uptake of 99m Tc-creatinine in blood did not change significantly during the present study, possibly due to a balanced exchange of creatinine between blood and tissues.…”
mentioning
confidence: 41%